Rheo‐NMR Spectroscopy for Cryogenic‐Probe‐Equipped NMR Instruments to Monitor Protein Aggregation. Issue 12 (5th December 2022) - Morimoto, Daichi; Walinda, Erik; Yamamoto, Akihiko; Scheler, Ulrich; Sugase, Kenji
Abstract: Cryogenic‐probe‐based Rheo‐NMR spectroscopy is a recently developed methodology to obtain solution NMR spectra of protein samples in situ under external shear. It is applicable to atomic‐resolution monitoring of protein aggregation in situ, thereby aiding understanding of the transient structural changes and state conversion of amyloidogenic proteins, which are strongly associated with the both the onset and the progression of neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease. Here, we present detailed experimental procedures for the instrumental setup and practical tips for preparation of NMR measurement to analyze protein aggregation by this technique. This protocol will thus aid future Rheo‐NMR spectroscopic studies not only of protein aggregation but also of other phenomena related to shear stress, such as shear‐induced viscosity increase and shear‐enhanced crystallization. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Setup of a Rheo‐NMR Instrument Basic Protocol 2 : Adjustment of the Vertical and Horizontal Positions of the Glass Stick Basic Protocol 3 : Monitoring Protein Aggregation by Rheo‐NMR Spectroscopy